2013
DOI: 10.1017/s1047951113000681
|View full text |Cite
|
Sign up to set email alerts
|

Foetal congenital heart disease: obstetric management and time to first cardiac intervention in babies delivered at a tertiary centre

Abstract: Vaginal delivery can be achieved in women delivering babies with major congenital heart disease at a tertiary centre. Delivery in or near a tertiary centre is recommended for patients requiring early intervention, of which many can be identified in advance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 20 publications
1
9
0
1
Order By: Relevance
“…Therefore, for most cases of CHD, vaginal delivery rather than scheduled cesarean delivery can be attempted because there is usually no need for immediate cardiac intervention after delivery [16].…”
Section: Congenital Heart Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, for most cases of CHD, vaginal delivery rather than scheduled cesarean delivery can be attempted because there is usually no need for immediate cardiac intervention after delivery [16].…”
Section: Congenital Heart Diseasementioning
confidence: 99%
“…Pregnant women carrying a fetus with fetal arrhythmias whose fetal heart rate during labor and delivery cannot be monitored adequately to reassure fetal wellbeing may need to be delivered by cesarean section. In addition, fetuses with established compromise such as those with fetal hydrops and growth restriction, especially when they cannot tolerate labor, may benefit from being delivered by cesarean section instead of having to undergo long inductions [16].…”
Section: Fetal Cardiac Arrhythmiasmentioning
confidence: 99%
“…Most of the pregnancies with foetuses heart defects should have vaginal deliveries in the third degree reference center however there is no direct translation into the follow-up of the newborns 25 .…”
Section: Copyright © 2017 Association For Prenatal Cardiology Developmentioning
confidence: 99%
“…Unfortunately, prenatal diagnosis can often lead to premature delivery at <37 weeks and higher rates of cesarean with no evidence of improved survival [73e75]. In fact, several studies have now shown that a vaginal delivery at term is preferred and elective cesarean should only be reserved for cases with a high likelihood for immediate postnatal intervention [76,77]. Perinatal and immediate postnatal management of fetuses with congenital birth defects are based on severity of fetal diagnosis, level of care needed, access to specialists, likelihood for rapid decompensation (hemodynamic instability) and need for immediate postnatal intervention with a lifesaving procedure.…”
Section: Perinatal Decision-making For Optimal Postnatal Transitionmentioning
confidence: 99%